POST-HARVEST HANDLING IN THE DRAGON FRUIT SUPPLY CHAIN - Sumardi Hadi Sumarlan (Journal of Engineering and Management in Industrial System, 2022)
Demand for dragon fruit is increasing every year. But to maintain and determine the quality of good dragon fruit, it is necessary to have information about the process of handling post-harvest when distributing dragon fruit ranging from farmers to consumers. Therefore, this study aims to examine the post-harvest handling process of dragon fruit in the dragon fruit supply chain cycle in Banyuwangi Regency. This study uses qualitative descriptive methods, where the main data sources used from direct field surveys. The supply chain of dragon fruit begins with the farmers-industrial/traditional market (Banyuwangi, Jakarta, Surabaya, Tangerang, Cikopo, Solo, Medan, and Riau). The post-harvest process carried out is grading based on size/weight and level of fruit defects, packaging using wooden crates, and the distribution process to the industry/market using a closed truck. Whereas in the industrial stage, post-harvest handling is done by cleaning, storing, and processing it into processed products.